Sains Islam Vs Sains Barat: Analisa Amalan Dan Perbandingan - Putri Elitya; Lailatus Sa’diah; Alfina Wildatul Fitriyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Western science and Islamic science are considered different in several aspects. This difference is very visible when Western science arrogantly claims that science is not related to religion and was not born from the church, while Islam believes that science cannot be separated from religion. This can happen because Western science is rooted in ratio while Islamic science is rooted in revelation. This view then gave birth to a dichotomy between general sciences and religious sciences. This is what then encourages Muslim scientists to carry out ijtihad for a paradigm change through the Islamization of science.